Validation of Competencies in E-Portfolios: A Qualitative Analysis - Zawacki-Richter, Olaf; Bäcker, Eva Maria; Hanft, Anke (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
This paper uses the example of an Internet-based advanced studies course to show how the portfolio method, as a competence-based form of examination, can be integrated in a blended learning design. Within the framework of a qualitative analysis of project portfolios, we examined which competencies are documented and how students reflected on their competence development process using portfolios.